Portrait of an American Gallery : The Pace Gallery New York. - The Pace Gallery, New York; Galerie Isy Brachot, Bruxelles (Bruxelles : Galerie Isy Brachot, 1990)
Calder, Alexander ; Chamberlain, John ; Close, Chuck ; Condo, George ; Cornell, Joseph ; Dine, Jim ; Dubuffet, Jean ; Jensen, Alfred ; Martin, Agnes ; Morley, Malcolm ; Nevelson, Louise ; Picasso, Pablo ; Reinhardt, Ad ; Rothko, Mark ; Samaras, Lucas ; Schnabel, Julian ; Steinberg, Saul
Portrait of an American Gallery : The Pace Gallery, New York, Galerie Isy Brachot, Bruxelles, 19.4 - 23.6.1990
boek